DI SEKITAR MASALAH AGAMA DAN KOHESI SOSIAL:PENGALAMAN DAN TANTANGAN - Taufik Abdullah (Jurnal Masyarakat dan Budaya, 2009)
Religion is the sacred relationship between human-being and the transcendent concept of Gidhead. But as a social and cultural phenomenon, religion is the strongest factor that determines the form and the strength of social integration and cohesion. In a plural society religion can become a barrier to an undifferentiated social cohesion. Looking religion as the sacred foundation of social relationship from historical perspective it may appear in four different faces, though by means exclusive to each others. Understanding on the teaching of the adhered can be the important source of social dynamics -- it is the basis of a certain form of social change. Secondly, despite the fact that science has consistently opened up the secrets and even the laws of nature, it cannot replace the role of religion as the source of the ultimate answer to the questions of the â€œrealâ€ reality. Third, religious pluralities and more importantly the differences in the understanding of the â€œtrue teachingsâ€ of the commonly adhered religion may become a source of internal conflict, although at the same it strengthens the internal cohesion of the believers of the same religious orientation. Four, in the conflict situation, the understanding of oneâ€™s religion can easily become a non-negotiable stand in the relation with the others. Despite its noble idea, the New Order -sponsored â€œthree strategies of harmonious lifeâ€-- the Pancasila, â€œthe three harmonious religious livesâ€ (among co-religionists, among the followers of different religions, and between religious followers and the government) and â€œthree brotherhood or uchuwah (Islamic, national, and intentional brotherhood) -- lost its credibility the moment the state undergone the crisis of legitimacy. The religion-based social cohesion can only be guaranted by a healthy democratric life and the continuing effort to strengthen the tradition of the spirit of tolerance. Keywords: Agama, kohesi sosial, Durkheim, Max Weber, struktural-fungsional, fenomenologi, â€œtiga strategi dasarâ€.